Characterisation and evaluation of morphological trials, biological features and seed yield of 23 flax accessions (Linum usitatissimum L.) of different geographical origins - Silska Grażyna; Bocianowski Jan (Herba Polonica, 2018)
Introduction: The Institute of Natural Fibres and Medicinal Plants (INF&MP) is involved in the protection of the genetic resources of flax (Linum usitatissimum L.) and hemp (Cannabis sativa L.). In 1998–2000, the INF&MP conducted research titled “Collection and evaluation of flax and hemp cultivars and ecotypes”. Poland participates in the programme, financed by the Ministry of Agriculture and Rural Development because our country has signed the Convention on Biological Diversity.